Prosesi Upacara Perkawinan Adat Bali Di Desa Duda Timur - Pawana, I Gede (PANGKAJA: JURNAL AGAMA HINDU, 2018)
Traditional Balinese wedding ceremonies in various forms adapt to local customs. This can be seen from the series of events, the ideas used, and the specific rules that apply to the bride. Like for example what happened in Duda Timur Village is a bit different from the traditions in the surrounding area. However, although the variations appear to be different, all of these traditions are patterned in preparation, im- plementation and post-implementation. In the village of Duda Timur itself, the preparatory ceremony begins with the selection of a good day which is very important, because the success of the ritual and the consequences of the future marriage are determined by the choice of the day. After the day is determined, according to the schedule the process will be carried out such as ngentenin, mebasan pupur, ngungkab lawang and mejauman. This article describes in detail the description of the implementation of the cer- emony from preparation to post-ceremony. Each stage is carried out well because there are symbols or messages to be conveyed and must be known by the bride, so that when they are married they are ready for their new life.